2019
DOI: 10.2196/11950
|View full text |Cite
|
Sign up to set email alerts
|

Using Exploratory Trials to Identify Relevant Contexts and Mechanisms in Complex Electronic Health Interventions: Evaluating the Electronic Patient-Reported Outcome Tool

Abstract: BackgroundDesigning appropriate studies for evaluating complex interventions, such as electronic health solutions to support integrated care, remains a methodological challenge. With the many moving parts of complex interventions, it is not always clear how program activities are connected to anticipated and unanticipated outcomes. Exploratory trials can be used to uncover determinants (or mechanisms) to inform content theory that underpins complex interventions before designing a full evaluation plan.Objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 48 publications
(53 reference statements)
0
47
0
Order By: Relevance
“…The only comparable study showed no effects on health-related quality of life [17], and problems with integration in GP-practices work ow [18]. Nevertheless, in supplementary interviews the patients still reported increased self-con dence and motivation as a result of the intervention [17].…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…The only comparable study showed no effects on health-related quality of life [17], and problems with integration in GP-practices work ow [18]. Nevertheless, in supplementary interviews the patients still reported increased self-con dence and motivation as a result of the intervention [17].…”
Section: Discussionmentioning
confidence: 93%
“…In order to be able to calculate a meaningful sample size for the study, recommendations refer to include at least 50 participants per arm to achieve a power of 80% and an effect size of d < 0.1 (2-side signi cance level of 5%) [34]. For the randomized trial we assumed a small effect size because studies measuring health-related quality of life with SF-12 with comparable populations showed no signi cant effects after four month [17] or showed signi cant effects at the earliest after 24 month [26]. Since the randomized study in this case has a duration of only six months, a lower effect would su ce as an indication of the effectiveness of 'TelePraCMan'.…”
Section: Sociodemographic Datamentioning
confidence: 99%
See 3 more Smart Citations